Pengaruh Financial Ratio dan Corporate Governance terhadap Financial Distress Perbankan Syariah Indonesia Periode 2013 – 2019 - Syaepullah, Rizky; Atmadji, Eko (Rifa'Institute, 2021)
Profitability and financing efficiency are the main indicators of changes in macroeconomic conditions. In theperiod 2015 – 2018, Islamic banking has not shown positive numbers in profitability and financing efficiency. This shows that the overall development of Islamic banking has not been able to maintain the level of financial health of the company. If Islamic banking cannot maintain the level of financial soundness, then the potential for Islamic banking to experience bankruptcy conditions begins with financial distress conditions becoming greater. This study aims to analyze the effect of financial ratio variables such as financial ratio variables, namely operating costs of operating income, capital adequacy ratio and current ratio and is focused on corporate governance consisting of the board of commissioners and the board of directors that affect financial distress in Islamic banking. Samples were selected by purposive sampling method as many as 14 sharia banks listed on the Indonesia Stock Exchange with a data collection period of 2013 – 2019. The data used is secondary data. Data analysis uses fixed effect model estimation and classic assumption test. The results showed that the variable financial ratio and corporate governance simultaneously affect the condition of financial distress. The conclusion of the study is that the board of directors does not have a significant positive effect on financial distress, but the capital adequacy ratio and current ratio have a significantly positive effect on financial distress. While the operational costs of operating income and the board of commissioners have a significant negative effect on financial distress conditions